Effect of Maternal Size, Reproductive Season and Interannual Variability in Offspring Provisioning of Carcinus maenas in a Coastal Lagoon - Rey, Felisa (2020)
Maternal effects and larval experience are considered the most important sources of variability in offspring phenotypes in marine invertebrates. Maternal provisioning during oogenesis is the first of a series of processes that will ultimately affect offspring phenotype and population dynamics. The keystone species of several European estuarine environments, Carcinus maenas, was used as a model to analyse the effect of female size and reproductive season on the fatty acid (FA) profile of newly extruded (stage 1) and ready-to-hatch (stage 3) embryos, as proxies for maternal investment and quality of newly hatched larvae, respectively. A total of 60 ovigerous females of two different sizes (carapace width [CW]: small CW <40 mm; large CW ≥40 mm) from Ria de Aveiro (Portugal) were sampled during three different reproductive periods: early reproductive season (ERS, late March/early April) 2012, ERS-2013 and late reproductive season (LRS; July) 2013. Maternal size was not a reliable indicator of maternal provision or larval quality at hatching. The interannual comparison (ERS-2012 vs. ERS-2013) revealed that the FA profile of stage 3 embryos was likely shaped by environmental conditions in the coastal lagoon during incubation. The seasonal comparison (ERS-2013 vs. LRS-2013) showed that embryos in the LRS had higher quality lipid content than embryos in the ERS, suggesting an increase of energetic reserves destined for reproduction in females in the LRS. Studies on maternal investment that overlook temporal variability should be interpreted with caution, especially in species inhabiting highly dynamic environments such as coastal lagoons and estuaries.